DENV-1 Infection of Macrophages Induces Pyroptosis and Causes Changes in MicroRNA Expression Profiles - Qinyi Zhang; Sicong Yu; Zhangnv Yang; Xingxing Wang; Jianhua Li; Lingxuan Su; Huijun Zhang; Xiuyu Lou; Haiyan Mao; Yi Sun; Lei Fang; Hao Yan; et al. (Biomedicines)
Background: Dengue virus (DENV) is the most widespread mosquito-borne virus, which can cause dengue fever with mild symptoms, or progress to fatal dengue hemorrhagic fever and dengue shock syndrome. As the main target cells of DENV, macrophages are responsible for the innate immune response against the virus. Methods: In this study, we investigated the role of pyroptosis in the pathogenic mechanism of dengue fever by examining the level of pyroptosis in DENV-1-infected macrophages and further screened differentially expressed microRNAs by high-throughput sequencing to predict microRNAs that could affect the pyroptosis of the macrophage. Results: Macrophages infected with DENV-1 were induced with decreased cell viability, decreased release of lactate dehydrogenase and IL-1β, activation of NLRP3 inflammasome and caspase-1, cleavage of GSDMD to produce an N-terminal fragment bound to cell membrane, and finally induced macrophage pyroptosis. MicroRNA expression profiles were obtained by sequencing macrophages from all periods of DENV-1 infection and comparing with the negative control. Sixty-three microRNAs differentially expressed in both the early and later stages of infection were also identified. In particular, miR-223-3p, miR-148a-3p, miR-125a-5p, miR-146a-5p and miR-34a-5p were recognized as small molecules that may be involved in the regulation of inflammation. Conclusions: In summary, this study aimed to understand the pathogenic mechanism of DENV through relevant molecular mechanisms and provide new targets for dengue-specific therapy.